Information technology: computers, communications and the Caribbean - Jefferson, Albertina ed. (ACURIL San JuanPR, 1989)
Covers topics such as the challenge of library automation; state of the art; telecommunications; electronic publishing; management of information technology; service delivery of information technology; and advances in library information technology.